The impact of the COVID-19 pandemic on hospital-treated self-harm in Sydney (Australia). (November 2022) - Sperandei, Sandro; Page, Andrew; Bandara, Piumee; Reis, Arianne; Saheb, Rowena; Gaur, Pankaj; Munasinghe, Sithum; Worne, Kathryn; Fozzard, Carolyn; Brakoulias, Vlasios
Objectives: This study investigated trends in hospital-treated self-harm and hospital presenting suicidal ideation in the period before and after COVID-19 public health responses by key socio-demographic groups among those presenting to hospitals in the Western Sydney (Australia) population catchment. Methods: Emergency department presentations for the period January 2016 to June 2021 were used to specify a series of interrupted time-series models to compare the observed and expected event rates of (1) hospital-treated self-harm and (2) hospital presenting suicidal ideation in the period following the onset of COVID-19 public health measures in March 2020. Rate differences between observed and expected rates in the post-implementation period were also estimated in models stratified by sex, age group, country of birth and socio-economic status. Results: There was no significant increase in hospital-treated self-harm in the period post-implementation of public health orders (March 2020) compared to the previous period, although there were lower than expected rates of emergency department presentations among non-Australian-born males, males aged 0–14 years and 25–44 years, and females aged 45–64 years. In contrast, there was a significant increase in hospital presenting suicidal ideation, particularly among women (rate difference per 100, 000 = 3.91, 95% confidence interval = [1.35, 6.48]) and those aged 15–24 years (both males and females, rate differences ranging from 8.91 to 19.04), and among those residing in lower socio-economic status areas (both males and females, rate differences ranging from 0.90 to 2.33). Conclusion: There was no increase in hospital-treated self-harm rates in the 15 months post-implementation of COVID-19 public health orders in Western Sydney; however, there was a significant increase in hospital presenting suicidal ideation. The limited change in suicidal behaviour may reflect the success of social and economic supports during this period, the benefits of which may have been different for young people, and those of lower socio-economic status.